Development Strategy for Agrotourism at PT. XPRO-AGROTAMA, Gunung Mulya Village, Tenjolaya District, Bogor Regency - Sayekti, Ayutyas; Jarwadi Budi Hernowo,; Nur Faizatul Luthfiah, (Jurnal Manajemen, 2025)
This study seeks to uncover critical elements, industry insights, and problems affecting the advancement of agribusiness and agrotourism at PT. Xpro Agrotama Cinangneng, located in Gunung Mulya Village, Tenjolaya District. The objective is to de-sign a plan utilising the Business Model Canvas to transition to agrotourism or agrotourism. Agrotourism integrates agriculture and tourism, allowing visitors to engage with rural life and farm-ing practices for enterprises such as PT. Xpro Agrotama, engaged in aquaculture and agrotourism, presents a promising prospect for diversification by utilising natural resources, human capital, and local attractions. The research employs the Business Model Can-vas to discern strategic opportunities. Business-to-business (B2B) and Business-to-Consumer (B2C) strategies are analysed, empha-sising customer trust, booking systems, visitor happiness, and re-source utilisation. Results indicate that PT. Xpro Agrotama em-phasises trust and dedication in its reservation methods while guaranteeing tourist happiness. The company effectively employs natural and human resources, providing nature and fishing tour-ism. PT. Xpro Agrotama possesses significant potential for expan-sion into agrotourism by capitalising on its internal strengths and external prospects. This technique may facilitate the development of tourism villages in Bogor Regency, fostering sustainable rural tourism and helping the local population.